Area group Learning Strategies by Using Brush Away Technique in Identifying Fine Motor and Art Skills for Kindergarden - Putri, Diana Kusuma; Raharjo, Tri Joko; Kustiono, Kustiono (Journal of Primary Education)
One strategy that can be done by the teachers to identify fine motoric and art skills is by using brush away technique. This study aimed to determine the effectiveness of abdominal brush away activities, to identify the advantages of brush away with other fine motoric activities in fine motoric and art skills of early childhood, and to know the difficulties of children in brush away activities. This research uses a qualitative descriptive approach. Data collection techniques using observation sheet instruments include anecdotal records and interviews. The data analysis in this study is using triangulation method through the description of the observation sheet. The results of this study are brush away technique makes it easy to identify fine motor and art skills for the early childhood, the advantage of brush away is there are some achievements in fine motor and art development in one activity, the children feel difficulty when they are cutting and rubbing the color with the fingers in brush away. In this research, it was found out brush away had just been introduced to the children, so some of them are not perfect when coloring in brush away activities by their fingers. The benefits of this research are as additional new knowledge in identifying fine motor and art skills for kindergarten and as a reference for future research.